A netnography of emergent ESOL researcher identity and development in a virtual community of practice - Chen, Julian; Greenier, Vincent; Janes, Sasha (Wiley-Blackwell, 2023)
For emerging researchers, communities of practice (CoPs) can be a much-needed source of knowledge and support, particularly during a global pandemic. Within this context, a virtual CoP (VCoP) project was initiated for novice researchers in Teaching English to Speakers of Other Languages (TESOL)/Applied Linguistics worldwide to exchange perspectives and academic knowledge. Guided by netnography, our study explores the social, cultural, and professional practices of VCoP through multiple digital sources, such as webinar recordings, Facebook group posts, reflective journal entries, and one-on-one interview. The triangulated data aims to examine the effects of virtual mentorship on the agency, engagement, and identity construction of an emerging researcher. Findings illustrate that a VCoP facilitates international networking, fosters the repositioning of ESOL researcher identity, and promotes agency through virtual mentoring. Specifically, netnography opens a viable avenue for remote data mining in Applied Linguistics research.